MAKSIM KESANTUNAN DALAM NOVEL DEAR NATHAN KARYA ERISCA FEBRIANI - Erni Pratiwi; Patriantoro Patriantoro; Amriani Amir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract.The research was to avoid the readers’ misunderstanding about speech acts of the novel. The research problem was about how the politeness maxim in the novel Dear Nathan by Erisca Febriani. The aim of this research was to describe the politeness maxim in the novel Dear Nathan by Erisca Febriani.This research was qualitative study with descriptive method. The technique in collecting data was documenter study with Speaking and context analysis. The data in this research were a dialog that in conformity with Politeness Maxim and a dialog with Politeness Maxim deviation. The data resource was the novel Dear Nathan by Erisca Febriani. The research implementation was associated with Indonesia language and literature learning that foundon 2013 Curriculum development in the first semester of X grade students of Senior Highschool. Basic Competence 3.11 where about analysing content, structure (orientation, submission, offer, agreement, closing) and the language of negotiation text. Based on the data analysis, it could be concluded that the utterances which in conformity with Politeness Maxim were more dominant than politeness principle deviation. Utterances that obey polite principle were 98 utterances. Utterances that deviate Politeness principle were 20 utterances. Keywords: maxim, novel, politeness, speech act